Systematics 2008 Programme and Abstracts - Gradstein, S. Robbert; Klatt, Simone; Normann, Felix; Weigelt, Patrick; Willmann, Rainer; Wilson, Rosemary (Universitätsverlag Göttingen, 2008)
The Göttingen conference "Systematics 2008" is the first joint meeting of the Gesellschaft für Biologische Systematik (GfBS) and the German Botanical Society, section Biodiversity and Evolutionary Biology (DBG), being the 10th Annual Meeting of the GfBS and the 18th International Symposium "Biodiversity and Evolutionary Biology" of the DBG. The conference programme covers biological systematics in the widest sense and provides ample opportunities for oral and poster presentations on new advances in plant, animal and microbial systematics. This volume brings together the abstracts of invited speaches from the plenary sessions on "Progress in Deep Phylogeny", "Speciation and Phylogeography", and "New Trends in Biological Systematics" as well as those of submitted talks and poster sessions.